The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.juro.2018.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury after Partial Nephrectomy of Solitary Kidneys: Impact on Long-Term Stability of Renal Function

Abstract: Acute kidney injury after partial nephrectomy was not a significant or independent predictor of long-term functional decline in our institutional cohort. A prospective study with larger sample sizes and longer followup is required to evaluate factors associated with long-term nephron stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 25 publications
2
42
0
3
Order By: Relevance
“…Overall, 2584 patients who underwent PN were evaluated for the final analyses. The median (interquartile [IQR]) American Society of Anesthesiologists (ASA) score was 2 (2)(3). In all, 72.4% of patients had clinical T1a (cT1a) stage tumours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 2584 patients who underwent PN were evaluated for the final analyses. The median (interquartile [IQR]) American Society of Anesthesiologists (ASA) score was 2 (2)(3). In all, 72.4% of patients had clinical T1a (cT1a) stage tumours.…”
Section: Resultsmentioning
confidence: 99%
“…We used these variables to construct a Introduction According to the latest AUA guidelines, partial nephrectomy (PN) should be preferred over radical nephrectomy (RN) for localised tumours, regardless of the surgical approach [1]. In fact, PN has comparable oncological outcomes with better preservation of renal function and a lower rate of long-term cardiovascular events compared to RN [2,3]. Nevertheless, PN is a technical challenging procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being the largest study of patients with RAPN in a solitary kidney, the sample size of 72 was relatively small and limits the overall generalizability of the results. Furthermore, we used the incidence of AKI as a measure of the degree to which SAC vs MAC impaired renal function, but it has been suggested that AKI after partial nephrectomy is not a strong indicator of long‐term function [19], in which case other measures of renal function, ranging from renal biopsy to Diethylenetriamine Pentaacetic Acid or an inulin‐like test, may provide more clarity. Possible confounders to renal impairment, including the pneumo level and the amount of normal parenchyma resected, were not considered because of a lack of recorded data.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary outcomes included the long-term functional change ratio (FCR) of GFR, which was defined as the most recent GFR/new baseline GFR after surgery [6]. New baseline GFR was defined as the latest value available during 3-12 months after surgery considering that renal function recovers after the initial drop immediately after surgery.…”
Section: Patient Data and Outcome Measurementsmentioning
confidence: 99%
“…As such, although a few previous studies have reported the association between AKI after nephrectomy and the risk of development of postoperative CKD, most studies analyzed a relatively small number of patients with different outcome definitions and used inadequate statistical analyses for the time-to-event outcome. As the appropriate statistical analyses were not selected, the linear relationship of the AKI stages with long-term renal functional change [6] or the graded association of AKI stages with CKD have not been evaluated. Therefore, we conducted a retrospective study evaluating the graded association of AKI stages with new-onset CKD and the linear association of AKI stages with renal functional change ratio from new-baseline renal function after radical nephrectomy to assess whether the association of AKI and CKD after radical nephrectomy is robust and has a dose-response relationship.…”
Section: Introductionmentioning
confidence: 99%